Hierarchy analysis and modeling on the Internet AS-level topology - GUO Hong1; YANG Bai-wei2; LAN Ju-long1; LIU Luo-kun2 (Tongxin xuebao)
Based on the in-depth analysis of he massive real AS-level topology data,the multi characteristics describing Internet AS-level topology’s hierarchy were abstracted,and a material way about network’s hierarchical partition were introduced,and the number of connected edged of adding new nodes and nonlinear probability were gived.Finally,a novel hierarchical dynamic evolution model named IAT-HDEM based on corenness and the k-core decomposition was proposed.The numerical simulations and analysis results showed that most of macroscopic statistics closed to real networks’,including power-law degree distribution and negative correlation clustering-degree distribution etc.